Antioxidant, Antibacterial Activity, and Chemical Composition Analysis of Habbatussauda (Nigella sativa) Products Circulating in Medan City Using GC-MS Method - Bangun, Sofia; Putra, Effendy; Haro, Ginda (Sciences and Clinical Pharmacy Research Journal, 2026)
Habbatussauda (Nigella sativa) products marketed in Medan City, Indonesia were analyzed to determine their chemical composition, antioxidant capacity, and antibacterial activity. Antioxidant activity was evaluated using DPPH, ABTS, and FRAP assays with UV-Vis spectrophotometry, while antibacterial activity was assessed by measuring inhibition zones against Staphylococcus aureus. Chemical constituents were identified using Gas Chromatography–Mass Spectrometry (GC-MS). The results showed that oil-based Habbatussauda preparations exhibited significantly higher antioxidant capacity and antibacterial activity compared to powdered products across all tested methods. GC-MS analysis revealed the presence of major bioactive compounds, including thymoquinone, dithymoquinone, and p-cymene, which are known to contribute to antioxidant and antibacterial effects. The findings indicate that the formulation type strongly influences the bioactivity of commercial Habbatussauda products. Oil-based preparations demonstrate superior functional properties and may offer greater therapeutic potential than powdered forms. This study provides scientific evidence to support informed consumer selection and quality evaluation of Habbatussauda products.